Android-Based Area Mapping in the Village of Kampunganyar - Banyuwangi - Mohammad Idhom; Budi Nugroho; Eva Yulia Puspaningrum (Nusantara Science and Technology Proceedings)
Kampunganyar is one of the villages located in Glagah District, Banyuwangi Regency. In this village the internet is connected smoothly that can be accessed by anyone. So it has called "Smart Kampung". This village has a lot of potential including tourism, plantations, agriculture, Micro Small and Medium Enterprises or known as UMKM. Many people do not know about the potential of this village. Therefore, in community service activities we built a mapping area system in Kampunganyar village that covers all potential areas with Android-based. In this system there is all information about the potential of the village in each region and its location. So that the general public can access the information through mobile devices freely. The public can find out what the tourism potential is and the location and photos of the tour. In addition, there are data on plantations and agriculture in several locations that can be known from this system. This system is very useful for marketing the potential of villages in the village of Kampunganyar so that it can be known by the general public.